Neuroepithelial tumors of the central nervous system with EWSR1::PATZ1 fusion: a case report and literature review - Feldmann, João Felipe Lima; Feldmann, João Henrique Lima; Canedo, Felipe Sales; Restini, Felipe Cicci Farinha; Mattedi, Romulo Loss; de Lima, Luiz Guilherme Cernaglia A.; Feher, Olavo (Frontiers in Oncology, 2025)
Neuroepithelial tumors (NEpT) harboring EWSR::PATZ1 fusions remain an enigma. Initially described in sarcomas, these tumors display remarkable histomorphological diversity and unpredictable clinical behavior based on histologic or molecular features, with no established management protocols. To date, this subgroup of neoplasms has not been acknowledged as a sui generis entity by the WHO classification system, and it is currently designated as ‘NEC’/’NOS’. This retrospective case series describes two young adults (32–35 years old) without cancer predisposition or risk factors, diagnosed with EWSR1::PATZ1-fused NEpT. Case 1, a female with seizures, presented a heterogeneous left parietal lobe lesion (4.0 × 3.2 × 3.6 cm), classified as high-grade NEpT with MGMT promoter methylation, a calibrated score of 0.95 (≥ 0.9), and a co-occurring somatic MUTYH mutation. Case 2, a male with chronic headaches and mild right-sided paresthesia, had a left frontotemporal lesion (3.0 × 2.8 × 3.4 cm), initially diagnosed as an extraventricular neurocytoma but later reclassified as a NEpT with low-to-intermediate grade features, without MGMT methylation, and a calibrated score of 0.92. Case 1 received upfront resection, followed by Stupp protocol chemoradiation and temozolomide maintenance, resulting in 14 months of progression-free survival (PFS). Case 2 underwent subtotal resection and adjuvant radiotherapy after an 8-month recurrence, achieving 11 months of PFS to date. Both patients are asymptomatic, off corticosteroids, with the latest imaging revealing no disease progression. Our cases emphasize that EWSR1::PATZ1-fused NEpT displays a unique signature (ventricular localization, glioneuronal differentiation, and a distinct methylation cluster), supporting their inclusion in the WHO classification. Moreover, we present the first documented somatic co-mutation involving MUTYH. At present, despite the theoretical risk of temozolomide resistance due to PATZ1 overexpression, our results suggest that conventional glioma therapies remain the preferred approach.